2019
DOI: 10.1101/548669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deconvolution of bulk blood eQTL effects into immune cell subpopulations

Abstract: Expression quantitative trait loci (eQTL) studies are used to interpret the function of disease-associated genetic risk factors. To date, most eQTL analyses have been conducted in bulk tissues, such as whole blood and tissue biopsies, which are likely to mask the cell type context of the eQTL regulatory effects. Although this context can be investigated by generating transcriptional profiles from purified cell subpopulations, the current methods are labor-intensive and expensive. Here we introduce a new method… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 41 publications
2
35
0
1
Order By: Relevance
“…Our downstream eQTL analysis in CBCS breast tumor expression also provided some insight into gene regulation, similar to recent work into deconvolving immune subpopulation eQTL signals from bulk blood eQTLs (101). In breast cancer, Geeleher et al previously showed that a similarly implemented interaction eQTL model gave better mapping of compartment-specific eQTLs (8,9).…”
Section: Unlike Traditional Reference-based Methods That Require Compsupporting
confidence: 68%
See 1 more Smart Citation
“…Our downstream eQTL analysis in CBCS breast tumor expression also provided some insight into gene regulation, similar to recent work into deconvolving immune subpopulation eQTL signals from bulk blood eQTLs (101). In breast cancer, Geeleher et al previously showed that a similarly implemented interaction eQTL model gave better mapping of compartment-specific eQTLs (8,9).…”
Section: Unlike Traditional Reference-based Methods That Require Compsupporting
confidence: 68%
“…We investigated how incorporating estimated compartment proportions affect cis-expression quantitative trait loci (cis-eQTL) mapping in breast tumors, a common application of deconvolution methods in assessing sources of variation in gene regulation (9,101). In previous eQTL studies using CBCS expression, several bulk breast tumor cis-eGenes (i.e.…”
Section: Incorporating Compartment Proportions Into Eqtl Models Detecmentioning
confidence: 99%
“…Technical covariates significantly associated with at least one PC (sequencing batch, RIN, age) were included in the model. In addition, because blood cell type composition can impact gene expression estimates in bulk RNA samples, we used DeconCell v. 0.1.0 23 to estimate the proportion of CD8T, CD4T, NK, B cells, monocytes and granulocytes in each sample (Supplementary table 2), and tested these for association with the first 10 PCs as described above. All covariates were significantly associated with at least one PC and were included in the differential expression model.…”
Section: Methodsmentioning
confidence: 99%
“…In order to simultaneously analyze two scales, the linear scale for heterogeneous cell mixing and the log/logit scale for trait effects, we applied nonlinear regression in omicwas (equations (4) and (5)). To cope with the multicollinearity of interaction terms, we applied ridge regularization (equations (9) and (10) The simulation data was generated from real datasets of DNA methylation and gene expression. The original cell type composition was retained for all samples, and the case-control status was randomly assigned.…”
Section: Evaluation In Simulated Datamentioning
confidence: 99%